Juridical Analysis of the Road Traffic and Transportation Law on the Regulation of Odong-Odong Vehicles on Highways in the Perspective of State Responsibility - Yudistira, Eka; Faitri, Anastasya Al; Stephanie, Putri Jeihan; Kartina, Ratu Mawar; Permana, Deni Yusup (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study discusses the legal issues surrounding odong-odong vehicles, which are categorized as illegal due to modifications that violate Law Number 22 of 2009 and Government Regulation Number 55 of 2012. Despite their illegality, these vehicles continue to operate, especially in urban areas, due to their social and economic value. Using a normative juridical method and Satjipto Rahardjo’s progressive legal approach, this study finds that current regulations are ineffective and cause legal and social tensions. The research suggests that revising existing laws to allow for the controlled legalization of odong-odong could offer benefits such as job creation and affordable transportation. It also highlights the need for central and local government roles in ensuring the safety and regulation of these vehicles.